A Scoping Review of Hope on Female Prisoners (Bangladesh Journal of Medical Science, 2023)
Prisoners are pressured from inside or outside the correctional facility, triggering psychological problems such as stress, anxiety, and depression. Meanwhile, hope is a positive psychology that helps inmates overcome psychological problems in correctional facilities. This study further aims to determine female prisoners’ hope in correctional facilities. The scoping review approach was used, starting with the article search through, EBSCO (CINAHL and Academic Search), ProQuest, and Google Scholar databases, using keywords such as female, hope, prisoners, and prison. The articles were sorted based on inclusion criteria, involving the availability of full texts, 2010-2021 publications, primary research results, population and research samples involving female prisoners, qualitative study, and the hope of female prisoners in prison. The results showed that female prisoners have hopes for life during their sentence and after being released from prison. As a conclusion, all the articles provided an overview of the hopes to be achieved ranging from career, family, education, desire to be free from crime, and the desire for revenge. Several articles demonstrated that the source of hope comes from social support while in prison, as well as religious, and self-development activities.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 482-488